The Effect of Digital Big Book Media on Descriptive Writing Skills of Students Elementary School - Sa'adah, Naily Alfi; Nuroh, Ermawati Zulikhatin (Journal Of Teaching And Learning In Elementary Education, 2024)
This research encourages student development through digital-based learning media, where most educators pay little attention to the application of media as a learning tool in the digital era. This study aims to determine the improvement of descriptive writing skills by using the application of digital big book media. The research method used was the quantitative one-group pre-test-post-test method. The population of this study were students of class IV B. The sample used in this study amounted to 21 students. Researchers used a descriptive writing skills assessment rubric that contained: Content, organization, grammar, style, spelling, and punctuation. The data collection technique used pre-test and post-test questions. The data analysis technique used paired t-tests. The results of this study indicate that there is an effect of digital big-book media on the descriptive writing skills of elementary school students. This can be seen from the results of the t-test with a sign (2-tailed) value of 0.000 <0.05, it can be said that Ho is rejected while Ha is accepted, meaning that digital big book media on descriptive writing skills has a positive effect on descriptive writing skills of elementary school students in class IV B SDN Karangjati III. Thus, digital big book media can be an innovation in learning in elementary schools and can be developed again with the needs of students, so that later it can foster students' creative ideas.